Novel approaches leading towards peptide GPCR de‐orphanisation. (3rd February 2020) - Hauser, Alexander S.; Gloriam, David E.; Bräuner‐Osborne, Hans; Foster, Simon R.
Abstract : The discovery of novel ligands for orphan GPCRs has profoundly affected our understanding of human biology, opening new opportunities for research, and ultimately for therapeutic development. Accordingly, much effort has been directed towards the remaining orphan receptors, yet the rate of GPCR de‐orphanisation has slowed in recent years. Here, we briefly review contemporary methodologies of de‐orphanisation and then highlight our recent integrated computational and experimental approach for discovery of novel peptide ligands for orphan GPCRs. We identified putative endogenous peptide ligands and found peptide receptor sequence and structural characteristics present in selected orphan receptors. With comprehensive pharmacological screening using three complementary assays, we discovered novel pairings of 17 peptides with five different orphan GPCRs and revealed potential additional ligands for nine peptide GPCRs. These promising findings lay the foundation for future studies on these peptides and receptors to characterise their roles in human physiology and disease.